The gender affirmative model : an interdisciplinary approach to supporting transgender and gender expansive children - Keo-Meier, Colt; Ehrensaft, Diane (Perspectives on sexual orientation and gender diversity series., 2018)
"This book aims to serve as a substantive guide to inform clinical work with prepubertal children according to the gender affirmative model (GAM). It provides the essential education for psychologists, other mental health providers and professionals from other disciplines to be able to provide culturally competent care to this population of children and their families. In addition, the book lays the groundwork for further dialogue on and research into developing sound practice for working with transgender and gender expansive (TGE) children and their families. All chapters examine the issue of TGE children from the perspectives of the individual, the family, and culture. The book focuses on children; because gender identity develops in early childhood and sexual orientation develops closer to puberty. The book is organized into thirteen chapters. Chapters two through six focus on the individual child in development and psychotherapy. It brings the reader through developmental theories of gender development, provides tools to sharpen skills at differentiating gender identity and expressions, increase consciousness about issues impacting TGE children of color, considers the accompanying psychological factors that often show up alongside gender creativity, and delves into trauma informed practice through the GAM lens. Chapter seven is a comprehensive child and family assessment guide. The next three chapters center on family dynamics and family therapy. Chapters 11 and 12 cover the interdisciplinary, collaborative, and intersectional nature of GAM providers. The final chapter brings up the current limitations of the GAM as well as ideas on where to go from here. (PsycINFO Database Record (c) 2018 APA, all rights reserved)"--Preface. (PsycINFO Database Record (c) 2018 APA, all rights reserved)